A Review of Numerical Techniques for Frictional Contact Analysis - Govind Vashishtha; Sumika Chauhan; Riya Singh; Manpreet Singh; Ghanshyam G. Tejani (Lubricants)
This review analyzes numerical techniques for frictional contact problems, highlighting their strengths and limitations in addressing inherent nonlinearities and computational demands. Finite element methods (FEM), while dominant due to versatility, often require computationally expensive iterative solutions. Alternative methods, like boundary element methods (BEM) and meshless methods, offer potential advantages but require further exploration for broader applicability. The choice of contact algorithm significantly impacts accuracy and efficiency; penalty methods, though computationally efficient, can lack accuracy at high friction coefficients; whereas, Lagrange multiplier methods, while more accurate, are computationally more demanding. The selection of an appropriate friction constitutive model is crucial; while the Coulomb friction law is common, more sophisticated models are necessary to represent real-world complexities, including surface roughness and temperature dependence. This review paper delves into the future research that prioritizes developing computationally efficient algorithms and parallel computing strategies. Advancements in constitutive modelling are vital for improved accuracy, along with enhanced contact detection algorithms for complex geometries and large deformations. Integrating experimental data and multiphysics capabilities will further enhance the reliability and applicability of these numerical techniques across various engineering applications. These advancements will ultimately improve the predictive power of simulations in diverse fields.